A Descriptive Study on the Role of Cinematographic Technology in the Effectiveness and Quality of Program Production at Bina Darma TV (BTV UBD) - Nurul Azizah; Desy Misnawati (Riviera Publishing, 2026)
The development of cinematographic technology in the modern media industry has transformed the paradigm of content production, including within academic environments. This study aims to analyze the role of cinematographic technology in enhancing the effectiveness and quality of program production at Bina Darma TV (BTV UBD), a digital campus-based media platform. Using a descriptive qualitative method, data were collected through in-depth interviews, direct observation, and documentation involving production crew members consisting of managers, producers, camera operators, and editors. The analysis was conducted based on the Miles and Huberman model and Mascelli's 5C Theory, which includes Camera Angles, Continuity, Cutting, Close-Ups, and Composition. The results indicate that the application of modern technologies — such as 4K cameras, gimbals, drones, professional lighting systems, and artificial intelligence (AI)-based software — enhances work effectiveness and production time efficiency, and yields broadcasts of higher visual, narrative, and audio quality. Nevertheless, challenges remain in terms of limited equipment, high maintenance costs, and uneven competence among student crews. In conclusion, cinematographic technology plays a vital role in strengthening professionalism and the university's branding, while also serving as a practical learning laboratory for students in the era of digital broadcasting.